What do you do for a living? Toward a more succinct definition of health services research - Phillips Charles D (BMC, 2006)
Abstract This commentary discusses the need for, and the advantages of, a more concise, revised definition of the field of health services research. It argues for a definition that includes not only the topics on which health services research focuses but also the goals of health services research. A number of condensed definitions are provided for consideration.